Analisis Kinerja Pegawai Rumah Sakit Pada Pengelolaan Keuangan Sejak Penerapan Blud Di RSUD Salewangang Kabupaten Maros - Reza Aril Ahri; Samsuar Samsuar; Nurmiati Muchlis (Journal of Muslim Community Health, 2021)
Background: Based on the results of the survey, while conducting the research, there were some obstacles during the research, which were caused when doing the research, there were some informants who were not willing to be interviewed and there were informants who were not there when doing the research. However, of the 5 people who became informants had provided in-depth information about the performance of employees in the financial division of the Salewangang Regional Hospital, Maros district. This study aims to analyze the performance of hospital employees in financial management since the implementation of BLUD in Salewangang Hospital, Maros Regency. Methods: As for this type of research, it is qualitative, this research was conducted at Salewangang Maros Hospital for 1 month.The informants in this study were 5 informants. Results: of the study showed that from the 5 key informants, information was found that employee performance was influenced by salary.